The Utilization of Family Medicinal Plants by The Community of Tebang Kacang Village, Kubu Raya Regency - Utari, Bela; Mariani, Yeni; Arbiastutie, Yanieta; Yusro, Fathul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Family medicinal plants (TOGA) are a form of traditional medicine still used independently by the community, especially by people living on the city's outskirts. Tebang Kacang Village is one of the villages within the administrative area of Kubu Raya Regency, but it is located on the outskirts of Pontianak. This research aims to analyze the use of family medicinal plants in the Tebang Kacang Village community, which is close to the provincial capital and has easy access to modern health facilities. A total of 311 respondents selected using purposive sampling were interviewed in-depth and with a questionnaire as a guide. They were asked about the use of family medicinal plants.The study results show that the people of Tebang Kacang Village still use medicinal plants, especially plants planted and cultivated around their home gardens and gardens or what is known as TOGA. The community used 75 species of plants belonging to 38 plant families. These plants are used not only to treat various diseases but also to care for people's health. The community also uses this family of medicinal plants as food in the form of vegetables and fruit. The people of Tebang Kacang Village mostly use the leaves (45%) and fruit (20%) of TOGA to make medicinal concoctions. These medicinal concoctions are generally prepared by grabbing (51.14%) and used by drinking (53.93%). This research shows that even though this village is relatively close to urban areas, people still choose to use medicinal plants to treat various diseases and maintain health. TOGA is the first choice of treatment.